2016
DOI: 10.1371/journal.pone.0153116
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Including Misidentified Sharks in Life History Analyses: A Case Study on the Grey Reef Shark Carcharhinus amblyrhynchos from Papua New Guinea

Abstract: Fisheries observer programs are used around the world to collect crucial information and samples that inform fisheries management. However, observer error may misidentify similar-looking shark species. This raises questions about the level of error that species misidentifications could introduce to estimates of species’ life history parameters. This study addressed these questions using the Grey Reef Shark Carcharhinus amblyrhynchos as a case study. Observer misidentification rates were quantified by validatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 31 publications
0
32
0
Order By: Relevance
“…One reason could be underestimation of the model parameters applied by Smith et al (1998) (age at maturity 7 years, maximum age 18 years, fecundity 2.5 pups yr -1 ) to generate an increase of 5.4% year -1 . Recent research has revised these variables to larger ranges (age at maturity of 9 -11 years; (Robbins 2006;Smart et al 2016), maximum age of 12 -19 years; (Radtke and Cailliet 1984;Robbins 2006;Smart et al 2016), fecundity of 1 -6 pups year -1 ; (Robbins 2006;Stevens and McLoughlin 1991;Wetherbee et al 1997) and C. amblyrhynchos in northern Australia has been found to have on average three pups year -1 (Stevens and McLoughlin 1991) and 3-4 pups year -1 on the Great Barrier Reef (Robbins 2006). The second model applied by Smith et al (1998) increased fecundities by 25%, a value more consistent with observed patterns, however population growth of 7.8% year -1 still remained well below the values required to obtain the rate of recovery we observed.…”
Section: Discussionmentioning
confidence: 99%
“…One reason could be underestimation of the model parameters applied by Smith et al (1998) (age at maturity 7 years, maximum age 18 years, fecundity 2.5 pups yr -1 ) to generate an increase of 5.4% year -1 . Recent research has revised these variables to larger ranges (age at maturity of 9 -11 years; (Robbins 2006;Smart et al 2016), maximum age of 12 -19 years; (Radtke and Cailliet 1984;Robbins 2006;Smart et al 2016), fecundity of 1 -6 pups year -1 ; (Robbins 2006;Stevens and McLoughlin 1991;Wetherbee et al 1997) and C. amblyrhynchos in northern Australia has been found to have on average three pups year -1 (Stevens and McLoughlin 1991) and 3-4 pups year -1 on the Great Barrier Reef (Robbins 2006). The second model applied by Smith et al (1998) increased fecundities by 25%, a value more consistent with observed patterns, however population growth of 7.8% year -1 still remained well below the values required to obtain the rate of recovery we observed.…”
Section: Discussionmentioning
confidence: 99%
“…When the same Leslie matrix models were applied to a different population of C. amblyrhynchos using the results of Smart et al. () in the present study, the inherent error within these models was far more apparent. Using life history estimates from the PNG population, the present study predicted negative population growth even if the population was unfished.…”
Section: Discussionmentioning
confidence: 63%
“…Indirect mortality estimates were more erroneous for the PNG population based on the results of Smart et al. () and were severely overestimated when compared to estimates from the Bayesian analysis. This was corrected by updating the demographic analyses for the PNG population with the Bayesian Z posteriors for the GBR population.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations